DIGITAL REALITY AS A NEW MANIFESTATION PHENOMENA OF BORDER CULTURE - Maria E. Kulyan-Kozionova; Maria V. Shimolina; Elena G. Shchekina (Russian Studies in Culture and Society)
This article is dedicated to the analysis of the phenomenon of cultural liminality and its manifestation through digital space, opening new possibilities for cross-cultural interaction and creating hybrid cultural forms. Studying the liminality of culture at the intersection of digital and real spaces will enhance our understanding of contemporary cultural transformations and current realities. The evolution of digital reality necessitates constant revision of theoretical approaches.